2021
DOI: 10.3390/cancers13102476
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of Circulating Tumor Cells in Patients with Hepatocellular Carcinoma Undergoing Surgical Resection or Liver Transplantation

Abstract: Background: In patients with hepatocellular carcinoma (HCC), a complete clearance of circulating tumor cells (CTCs) early after liver transplantation (LT) or surgical resection (LR) could prevent tumor recurrence. Methods: prospective pilot study including patients with HCC who underwent LR or LT from September 2017 to May 2020. Enumeration of CTCs was performed in peripheral blood samples (7 mL) using the Isoflux® system (Fluxion Biosciences) immediately before surgery, at post-operative day 5 and at day 30. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
(50 reference statements)
1
13
0
Order By: Relevance
“…Very recently, Hwang et al have shown that CTCs with cancer stemness could predict HCC recurrence when they are detected preoperatively and 1 day after LT using fluorescent activated cell sorter [ 96 ]. We have evaluated the clearance kinetics of CTCs in HCC patients undergoing LT and found that the presence of CTC clusters before surgery was associated with an incomplete clearance of CTCs at postoperative day 30, which in turn predicted mortality due to extrahepatic recurrence of HCC [ 98 ]. The unpredictable evolution of CTCs after LT could be in part explained using immunosuppressive drugs, which are required to prevent graft rejection.…”
Section: Dynamic Changes Of Ctc Counts After Hcc Therapymentioning
confidence: 99%
“…Very recently, Hwang et al have shown that CTCs with cancer stemness could predict HCC recurrence when they are detected preoperatively and 1 day after LT using fluorescent activated cell sorter [ 96 ]. We have evaluated the clearance kinetics of CTCs in HCC patients undergoing LT and found that the presence of CTC clusters before surgery was associated with an incomplete clearance of CTCs at postoperative day 30, which in turn predicted mortality due to extrahepatic recurrence of HCC [ 98 ]. The unpredictable evolution of CTCs after LT could be in part explained using immunosuppressive drugs, which are required to prevent graft rejection.…”
Section: Dynamic Changes Of Ctc Counts After Hcc Therapymentioning
confidence: 99%
“…The IsoFlux TM system (Fluxion Biosciences, Inc., Alameda, CA, USA) is a semi-automatic platform for the enrichment of CTCs using a combination of immunomagnetic positive selection and microfluidics, and it significantly increases isolation efficiencies compared to the FDA-approved CellSearch ® (Menarini, Italy) system [ 5 ]. An improvement in the recovery rate from 40% to 90% using cancer cell lines was achieved compared with CellSearch ® [ 6 ], and this technology was used to successfully isolate CTCs in bladder [ 7 ], prostate [ 8 ], ovarian [ 9 ], liver [ 10 , 11 , 12 , 13 ] and pancreatic [ 14 ] cancer patients. However, it was only recently that the IsoFlux TM (Fluxion, Biosciences, Inc., Alameda, CA, USA) platform was used to isolate CTCs from colorectal cancer patients to evaluate the relationship between microsatellite instability (MSI) status and peri-operative release of CTCs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the selected studies. Among 13 articles, only eight studies specifically focused on LT ( 19 26 ) ( Table 1 ), including only transplant patients, whereas five other studies investigated CTCs in cohorts of patients receiving various treatments ( 27 31 ).…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Recently, Amado et al. studied the kinetics of CTCs clearance after LR and LT, utilizing iFISH ® and collecting sequential blood samples pre-operatively, on post-operative day (POD) 5 and POD30 ( 27 ). Despite a comparable preoperative CTCs count, LT was followed by a significant proportion of CTCs clearance ( p = 0.007), conversely to LR ( p = 0.241).…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%